Effect of storage temperatures on the quality parameters of fish condiment prepared from Thai pangus (Pangasianodon hypophthalamus): Quality parameters of fish condiment (Journal of the Bangladesh Agricultural University, 2019)
Quality parameters of a fish/food product changes with the storage temperature. Therefore, the present study was carried out to evaluate the effect of different storage temperatures on the changes in chemical and microbiological parameters of fish condiment prepared from Thai pangus (Pangasianodon hypophthalmus). The study was conducted in the Department of Fisheries Technology Laboratory from October 2015 to September 2016.Standard methodologies for product preparation and other analyses (chemical and microbiological) with some modifications were followed. The results of the experiment showed that- irrespective of storage temperature the TVB-N value increased progressively with the lapse of storage period. At room temperature (28°C to 32°C), the values increased very rapidly in compare to those of refrigeration (5°C to 8°C) and frozen temperature (-18°C to -20°C). The TVBN value increased from 1.63±0.01 to 3.31±0.06, 3.18±0.02 and 2.02±0.02 mg/100g on day 15th at room, 90th at refrigeration and 120th at frozen storage temperature, respectively. On the other hand, the peroxide values increased from 2.80±0.10 to 6.08±0.10, 6.97±0.20 and 5.40±0.20 meq/kg of oil, on 15th at room, 90th at refrigeration and 120th at frozen storage temperature, respectively. Throughout the storage period, the pH values of fish condiment also changed at different temperatures. The pH value decreased from 5.24±0.01 to 4.75±0.05, 4.51±0.11 and 4.49±0.90, respectively on day 15th at room, day 90th at refrigeration and day 120th at frozen storage temperature. The bacterial load (CFU/g) in condiment was found to increase at room temperatures (from 2.2 ×104 to 2.6×107). However, the growth of bacteria was slower at refrigeration temperature (from 2.2 ×104 to 2.5×107) and at frozen temperature bacterial growth found negative (from 2.2 ×104 to 3.6×102). So, from the observation on the changes in different quality parameters at different storage temperatures, it could be concluded that, the shelf life of Thai pangus fish condiment at room temperature was shorter but at refrigeration temperature fish condiment may remain in acceptable condition more than 90 days and more than 120 days at frozen temperature.J Bangladesh Agril Univ 17(3): 417–423, 2019